If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (2x + -1)(3x + -1) Reorder the terms: y = (-1 + 2x)(3x + -1) Reorder the terms: y = (-1 + 2x)(-1 + 3x) Multiply (-1 + 2x) * (-1 + 3x) y = (-1(-1 + 3x) + 2x * (-1 + 3x)) y = ((-1 * -1 + 3x * -1) + 2x * (-1 + 3x)) y = ((1 + -3x) + 2x * (-1 + 3x)) y = (1 + -3x + (-1 * 2x + 3x * 2x)) y = (1 + -3x + (-2x + 6x2)) Combine like terms: -3x + -2x = -5x y = (1 + -5x + 6x2) Solving y = 1 + -5x + 6x2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 1 + -5x + 6x2
| 4-√-12/4 | | t=16.11-0.0062 | | -7t^2+7t+8t^3-t^3+15t^2-4t= | | 5+8(X-2)=11-7(X-8) | | x(x-6)-x^2-5x-7=0 | | p(x)=(500-x)/20 | | X/100=27/64 | | x(x-6)=x^2+5x+7 | | -4(x-9)=-9x+6 | | -7(t-8)-(t+3)=10 | | X+6y+4z=-13 | | (4x+2)(2x+1)=0 | | x=5000/40/x-10/x | | 4x-9=-18 | | .15x=3800 | | -3x-Y-z=-6 | | 7x+54=9(x+6)-2x | | t-1/4=7/4 | | 5+8(x-2)=7(x-8) | | x*12=44800 | | x*44800= | | -4+4x=4(x-1) | | 8y=16+-2x | | -.25x+x^2=-.1875 | | 2x+8+2x+8+64=180 | | 29/9=100/n | | 140=(n-2)*180/n | | 21=7b | | 4x+5y+2z=x | | N+3p=0 | | (x+6)(x-5)=-10 | | 40=5/x |